A method for comparison of large deflection in beams - Taghipour, Yasser; Darfarin, Sara (Zielona Góra: Uniwersytet Zielonogórski)
The deflection analysis of beams has been recently an active area of research. The large deflection of beams refers to deflections occurring due to large displacements and small strains. This type of deflection has been one of the areas of interest in the development of beam deformation methods. The wide diversity of beam deformation methods highlights the importance of their comparison to further elucidate the properties and features of each method and determine their benefits and limitations.
Keywords: comparison method; beam; large deflection; displacement function; strain